-4v-9=-6-v

Simple and best practice solution for -4v-9=-6-v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4v-9=-6-v equation:


Simplifying
-4v + -9 = -6 + -1v

Reorder the terms:
-9 + -4v = -6 + -1v

Solving
-9 + -4v = -6 + -1v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add 'v' to each side of the equation.
-9 + -4v + v = -6 + -1v + v

Combine like terms: -4v + v = -3v
-9 + -3v = -6 + -1v + v

Combine like terms: -1v + v = 0
-9 + -3v = -6 + 0
-9 + -3v = -6

Add '9' to each side of the equation.
-9 + 9 + -3v = -6 + 9

Combine like terms: -9 + 9 = 0
0 + -3v = -6 + 9
-3v = -6 + 9

Combine like terms: -6 + 9 = 3
-3v = 3

Divide each side by '-3'.
v = -1

Simplifying
v = -1

See similar equations:

| 12+50-14= | | -4(x+2)-44=8-36 | | 3x+13+3=2xsquared | | 10x=4(-2x+9) | | 6-5y=-4-6y | | 4x-2+3x= | | 46h=4h^3+5h^2 | | -7x-11y-5x+15y= | | -5x+18-3(x-1)=8x-(7x-9)+6x+6 | | V(x)=33x+162findx | | 12z+17=11z | | C=38.17+0.50 | | 2z^8/7z^7 | | v=144(3.14) | | 4(w-13)+17=19 | | -9x-5(3-4x)=6(x-4)-36 | | -7(x+4)= | | X=-(-10)/2(-5) | | 6h-h+2=17 | | 3x+7(x-9)=3(x-14) | | 6x+7=7x-1 | | Sin=-2 | | 14-w=17 | | cosz=-2 | | -1/2=3/5y-1/3 | | 9(3a+8)= | | cosz=-3 | | 4x^4/6/5x^3/6 | | -1/3v-1/2=-3/7 | | 12+2j=-j | | 5X=245 | | Y=-4x^2+16x-16 |

Equations solver categories